2014
DOI: 10.1097/mot.0000000000000098
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the role of mTOR and metabolism in T cells reveals new potential approaches to preventing graft rejection

Abstract: Purpose of review In this review, we discuss the recent advances with regard to the mTOR signaling pathway and focus on how this pathway modulates immune responses. Overall, these insights provide important clues in terms of strategically integrating mTOR and metabolic inhibitors into transplantation rejection protocols. Recent findings mTOR is regulated by environmental cues and activates diverse downstream pathways to guide cell growth and fate. What has emerged from recent studies is that mechanistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 105 publications
1
27
0
Order By: Relevance
“…Further, even though we observed 100% heart graft survival (Figure 4D) while the mice were being treated, preliminary studies indicate that stopping therapy resulted in the eventual rejection of the hearts approximately 80 days later (data not shown). To this end, we are actively pursuing integrating tolerance inducing therapy such as costimulatory blockade with our anti-metabolic regimen (Bestard et al, 2011; Lo et al, 2014; Oderup et al, 2006; Pilon et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Further, even though we observed 100% heart graft survival (Figure 4D) while the mice were being treated, preliminary studies indicate that stopping therapy resulted in the eventual rejection of the hearts approximately 80 days later (data not shown). To this end, we are actively pursuing integrating tolerance inducing therapy such as costimulatory blockade with our anti-metabolic regimen (Bestard et al, 2011; Lo et al, 2014; Oderup et al, 2006; Pilon et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…This compound (also known as sirolimus) is a potent immunosuppressant that could result in tolerance and has been used extensively in transplantation [40-42]. Study of its downstream target, the mechanistic target of rapamycin (mTOR), revealed that costimulation, the net sum of positive costimulatory and negative coinhibitory signals, was routed in part through mTOR.…”
Section: Introductionmentioning
confidence: 99%
“…It also has an impact on effector T cell metabolic programming and TReg generation and maintenance. 124 In addition, Sirolimus was shown in vitro to reduce LT antigen replication but not BK virus DNA replication. 125 This could also occur in vivo and provide direct antiviral effects.…”
Section: Sirolimusmentioning
confidence: 99%